RG study of a non-local sine-Gordon model - Naón, Carlos María (2003)
We study a non-local version of the sine-Gordon model connected to a many-body system with backward and umklapp scattering processes. Using renormalization group methods we derive the flow equations for the couplings and show how non-locality affects the gap in the spectrum of charge-density excitations. We compare our results with previous predictions obtained through the self-consistent harmonic approximation.